2022
DOI: 10.3390/ijms23168849
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Infiltration by Treg and Th17 Cells as an Immune Response to Propionibacterium acnes Infection in the Course of Benign Prostatic Hyperplasia and Prostate Cancer

Abstract: Benign prostatic hyperplasia (BPH) and prostate cancer (PCa) belong to the most frequent diseases in ageing men. It has been proposed that prostate chronic inflammation is a risk factor for the development of both BPH and PCa. However, potential stimuli that cause or maintain inflammation in the prostate gland are still poorly characterized. Bacterial infections seems to be one of the potential sources of prostatitis. Recent studies show that Propionibacterium acnes (P. acnes) is the most prevalent microorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…It is believed that these changes could be linked to the severity of Cervical Intraepithelial Neoplasia (CIN), with an increase in Bacillus and Anaerococcus and a decrease in Gardnerella vaginalis potentially indicating a greater severity of the condition [ 36 ]. There are some studies suggesting that Propionibacterium acnes contributes to the development of several diseases in the prostate [ 37 ], gastric cancer [ 38 ], and ovarian cancer via regulating the hedgehog signaling pathway [ 32 ]. In this study, it was suggested that the genus level of Propionibacterium may be responsible for converting the cyst fluid environment to an environment with a lower concentration of iron.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that these changes could be linked to the severity of Cervical Intraepithelial Neoplasia (CIN), with an increase in Bacillus and Anaerococcus and a decrease in Gardnerella vaginalis potentially indicating a greater severity of the condition [ 36 ]. There are some studies suggesting that Propionibacterium acnes contributes to the development of several diseases in the prostate [ 37 ], gastric cancer [ 38 ], and ovarian cancer via regulating the hedgehog signaling pathway [ 32 ]. In this study, it was suggested that the genus level of Propionibacterium may be responsible for converting the cyst fluid environment to an environment with a lower concentration of iron.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been described that the presence of C. acnes in patients with prostate cancer correlates to a higher infiltration of regulatory T CD4(+), FoxP3(+) cells in prostatic tissues. Scientists discovered also that this infiltration correlates to the aggressiveness of the prostatic cancer in patients positive for C. acnes [13].…”
Section: Acnes Clinical Relevancementioning
confidence: 99%
“…Propionibacterium acnes ( P. acnes ) is the most common microorganism in normal prostate tissues and is abundant in PCa tissues. It can activate the cGAS-STING pathway and induce the expression of IFN, which subsequently promotes PCa growth [ 128 , 129 ].…”
Section: Neoplasmsmentioning
confidence: 99%